Intraperitoneal microdialysis detects intestinal leakage earlier than hemodynamic surveillance and systemic inflammation in a pig model. (1st February 2021) - Pischke, Soeren Erik; Hødnebø, Stina; Wester, Torjus; Haugaa, Håkon; Kvernebo, Knut; Barratt-Due, Andreas; Tønnessen, Tor Inge
Abstract: Objective: Anastomotic leakage is a common complication following large abdominal surgery, often developing to life-threatening abdominal sepsis due to late diagnosis. Currently, diagnostics rely on systemic hemodynamic and infection monitoring. We hypothesized that intraperitoneal microdialysis allows detection of peritonitis prior to changes in standard clinical parameters in a pig model. Materials and Methods: We included six pigs; five underwent intraperitoneal fecal contamination, one had sham surgery for a total of 10 h. Microdialysis was established in four intraabdominal quadrants and two hepatic lobes. All pigs were hemodynamically monitored with pulmonary artery and femoral artery catheters. Blood samples were assessed for inflammatory markers, terminal complement complex (TCC), interleukin (IL)-6, IL-10, and plasminogen activator inhibitor-1 (PAI-1). Results: Microdialysis showed intraperitoneal lactate increase during the first two hours after fecal contamination, which remained elevated throughout the observation time with concurrent decrease of glucose. Arterial lactate remained within reference range (<1, 6mM). Systemic inflammatory markers TCC, IL-6, IL-10 and PAI-1 increased significantly after minimum four hours. Mean arterial pressure, stroke volume variation and cardiac output were not compromised the first five hours. Sham surgery did not influence any of the parameters. Conclusion: Intraperitoneal fecal contamination leads to a rapid and pronounced intraperitoneal increase in lactate, decrease in glucose while pyruvate and glycerol levels remain unchanged. This distinct metabolic pattern of peritoneal inflammation can be easily detected by microdialysis. Observation of this pattern may minimize time to safe diagnosis of intestinal perforations after intraperitoneal fecal contamination.